Advancing landscape and seascape restoration: The case for policy coherence and good practice sharing - Keith, Bradby; Meseret, Carver; Chazdon, Robin; Louise, Combret; Kris, Decleer; Anita, Diederichsen; Rocio, Diaz-Chavez; Juliana, Echeverri; Milena, Engel; Estrada Carmona, Natalia; Gonzalez, Maggie; Boze, Hancock; et al. (2025)
Fragmented efforts are inadequate to address the systemic and highly interconnected challenges of our time. Responding effectively to runaway climate change, environmental degradation, biodiversity loss, and the spiralling socioeconomic crisis requires transformative governance built on partnerships that operate across space and time and are guided by a long-term vision for the future. To transform governance, policy coherence is needed across scales and over time, at local, landscape and seascape, national, regional, and global levels. Landscape and seascape restoration approaches that embed shared understanding and partnership in their design and implementation can help to foster policy coherence and thereby enable transformative governance. The brief discusses why policy coherence is a prerequisite for effective landscape and seascape restoration and, in turn, how landscape and seascape restoration can increase coherence across sectors, scales and time by aligning ecological, social and economic goals. It highlights the importance of gathering and sharing good practices to support policy integration and effective governance in landscape and seascape restoration. The brief is intended for government actors, practitioners, researchers, financiers, and civil society actors engaged in landscape and seascape restoration, and offers targeted recommendations to enable more resilient, inclusive, and transformative outcomes.